2012
DOI: 10.1111/j.1600-0501.2012.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of crestal bone by implant design. A comparative study in minipigs

Abstract: Greater bone preservation was observed for the AOI and SBLI compared with the NBTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
(46 reference statements)
6
32
0
Order By: Relevance
“…This implication points to a limitation of the present study, whereas it has two important variables that may influence the peri‐implant marginal bone reabsorption, the horizontal offset of the implant/abutment interface and the position of the implant platform in relation to the bone crest. Furthermore, the dimension of bone resorption/remodelling observed for TL implants in the present study was in agreement with other clinical studies, which have reported minimal bone loss in those implants (Blanes et al., ; Hanggi et al., ; Weber et al., ) supporting the validity of TL implants as a control group (Heitz‐Mayfield et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This implication points to a limitation of the present study, whereas it has two important variables that may influence the peri‐implant marginal bone reabsorption, the horizontal offset of the implant/abutment interface and the position of the implant platform in relation to the bone crest. Furthermore, the dimension of bone resorption/remodelling observed for TL implants in the present study was in agreement with other clinical studies, which have reported minimal bone loss in those implants (Blanes et al., ; Hanggi et al., ; Weber et al., ) supporting the validity of TL implants as a control group (Heitz‐Mayfield et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…The comparison between TL and BL implants was also performed in one animal (Heitz‐Mayfield et al., ) and two clinical (Chappuis et al., ; Fernández‐Formoso et al., ) studies. In a comparative study involving mini pigs, Heitz‐Mayfield et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the mean radiographic bone level is 0.4 mm above the implant's coronal aspect in the flapless group at 15 months. The minimum bone loss observed in the current study may be attributed to the specific implant design used (micro‐threaded, platform‐switching with a nanostructured surface) 24 . However, it is important to note that the implants in the flapless group were placed an average of 0.85 mm subcrestally at baseline, which may account for this result.…”
Section: Discussionmentioning
confidence: 67%
“…In an in vivo rabbit model, the OSP surface presented significantly higher bone response at 2 weeks as compared to an anodized surface presenting micrometer-level texturing [143]. In a crestal bone maintenance study conducted in minipigs by Heitz-Mayfield et al [144], both OSP and SLA implant surfaces presented higher degrees of crestal bone maintenance as compared to an implant having an anodized surface with micrometer-level texturing [144].…”
Section: Preclinical In Vivo Modelsmentioning
confidence: 94%